Quercetin Mitigates Methamphetamine-Induced Anxiety-Like Behavior Through Ameliorating Mitochondrial Dysfunction and Neuroinflammation - Chen, Fengrong; Sun, Jiaxue; Chen, Cheng; Zhang, Yongjin; Zou, Lei; Zhang, Zunyue; Chen, Minghui; Wu, Hongjin; Tian, Weiwei; Liu, Yu; Xu, Yu; Luo, Huayou; et al. (Frontiers in Molecular Neuroscience, 2022)
Methamphetamine (MA) abuse results in neurotoxic outcomes, including increased anxiety and depression. Studies have reported an association between MA exposure and anxiety, nonetheless, the underlying mechanism remains elusive. In the present study, we developed a mouse model of anxiety-like behavior induced by MA administration. RNA-seq was then performed to profile the gene expression patterns of hippocampus (HIPP), and the differentially expressed genes (DEGs) were significantly enriched in signaling pathways related to psychiatric disorders and mitochondrial function. Based on these, mitochondria was hypothesized to be involved in MA-induced anxiety. Quercetin, as a mitochondrial protector, was used to investigate whether to be a potential treatment for MA-induced anxiety; accordingly, it alleviated anxiety-like behavior and improved mitochondrial impairment in vivo. Further experiments in vitro suggested that quercetin alleviated the dysfunction and morphological abnormalities of mitochondria induced by MA, via decreasing the levels of reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and increasing the oxygen consumption rate (OCR) and ATP production. Moreover, the study examined the effect of quercetin on astrocytes activation and neuroinflammation, and the results indicated that it significantly attenuated the activation of astrocytes and reduced the levels of IL-1β, TNFα but not IL-6. In light of these findings, quantitative evidence is presented in the study supporting the view that MA can evoke anxiety-like behavior via the induction of mitochondrial dysfunction. Quercetin exerted antipsychotic activity through modulation of mitochondrial function and neuroinflammation, suggesting its potential for further therapeutic development in MA-induced anxiety.